Comparison of Sonographic Findings of the Rotator Cuff Between Diabetic and Non-diabetic Patients with Shoulder Pain - Shingh, Shashi Shekhar; Joshi, Birendra Raj; Thapa, Sunil S (Journal of Nepal Health Research Council, 2021)
Background: The aim of study is to evaluate the shoulder by sonography in patients presenting with shoulder pain and correlate the findings observed with the diabetic patient. Methods: Study was done in 60 patients who presented in the Department of Orthopedics with a history of the shoulder pain. Shoulder ultrasound was performed according to standard protocol, thickness of the supraspinatus tendon, presence of the tear, biceps tendon subacromial subdeltoid effusion and subacromial impingement were assessed. Results: Of the 60 patients, 46 were male and 14 were female. Among them 15 patients were diabetics, 12 patient were male and 3 patient were female. Supraspinatus(SST) tendon thickness was greater in diabetics than in non-diabetics. Similarly, Subacromial bursal effusion, Biceps tendon effusion and Subacromial impingement were also seen in greater frequency in diabetic patients. However, no significant correlation was found between tear and the diabetes. Conclusions: There was increased supraspinatus tendon thickness, subacromial impingement, subacromial bursal effusion and biceps tendon effusion in diabetic patient compared to non-diabetic patient. Keywords: Diabetes; rotator cuff; supraspinatus tendon; ultrasound